2006
DOI: 10.1080/10408390591000929
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Postmortem Aging in Fish: Understanding of Proteolysis and Disorganization of the Myofibrillar Structure

Abstract: Postmortem tenderization is caused by enzymatic degradation of key structural proteins in myofibrils as well as in extracellular matrix, and of proteins involved in intermyofibrillar linkages and linkages between myofibrils and the sarcolemma. The function of these proteins is to maintain the structural integrity of myofibrils. Current data indicate that calpains and cathepsins may be responsible for degradation of these proteins. Other phenomena occurring in cells postmortem (pH drop, sarcoplasmic Ca2+ increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
3
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(194 citation statements)
references
References 141 publications
(92 reference statements)
8
177
3
6
Order By: Relevance
“…0.05). Previous studies indicated that the fish death triggers autolysis and subsequently the muscle becomes softer and less elastic, and the process is accelerated by microbial activity (Delbarre-Ladrat et al, 2006). We proposed that texture properties of hardness, gumminess, and chewiness in pompano can be improved by RE þ N treatment during chilled storage.…”
Section: Texture Analysesmentioning
confidence: 92%
See 1 more Smart Citation
“…0.05). Previous studies indicated that the fish death triggers autolysis and subsequently the muscle becomes softer and less elastic, and the process is accelerated by microbial activity (Delbarre-Ladrat et al, 2006). We proposed that texture properties of hardness, gumminess, and chewiness in pompano can be improved by RE þ N treatment during chilled storage.…”
Section: Texture Analysesmentioning
confidence: 92%
“…The content of those two productions are the most extensive indicators to assess the quality of fish products (Delbarre-Ladrat, Cheret, Taylor, & Verrez- Bagnis, 2006).…”
Section: Total Volatile Basic Nitrogen and Trimethylamine Analysesmentioning
confidence: 99%
“…To meet the energy demands of tail flipping and in a variety of other physiological circumstances, such fast-type muscles utilize anaerobic energy pathways (mainly glycolytic fermentation) (Ellington 1983). Reduced ATP production, L-lactate accumulation and glycogen depletion are the consequence of this fermentative glycolysis in both crustaceans (Paterson 1993;Hervant et al 1999) and vertebrates (Bayliss 1995;Delbarre-Ladrat et al 2006;Neath et al 2007;Scheffler & Gerrard 2007).…”
Section: Introductionmentioning
confidence: 99%
“…TMA-N production in fish and fishery products is due to enzymatic and microbial degradation of protein and non-protein nitrogenous compounds. The protein and non-protein nitrogenous content in fish depends on several factors such as age, sex, culture method and locality of fish in which it resides [62]. The increase in TMA-N levels may result from domination of free amino acid, oxidation of amines and degradation of nucleotides by autolytic enzymes and microbial activity [63].…”
Section: Changes In Free Fatty Acids (Ffa)mentioning
confidence: 99%